2019
DOI: 10.1021/acsabm.9b00343
|View full text |Cite|
|
Sign up to set email alerts
|

Gold Nanorods Embedded in Polymeric Film for Killing Bacteria by Generating Reactive Oxygen Species with Light

Abstract: For the first time, anisotropic gold nanorods (AuNRs) were embedded with a photosensitizer dye (crystal violet) in polyurethane (PU) matrix to create the effective antimicrobial film, capable of killing Gram-negative bacteria on its surface when exposed to white light. The dye, when activated with white light, interacts with the AuNRs to generate reactive oxygen species (ROS), which kill bacteria. With a proper control of the aspect ratio (2.1−2.4) and coating of the AuNRs, the film can be tuned to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…It has been shown from previous work that the electrostatic interaction brings the dyes and the AuNRs together. 15 The overlapping between the absorption of the SPR peaks of AuNRs indicated by the simulation and the dye absorption confirm that all the components of the spectra, can participate in the plasmonic coupling with the dye. Thus, when located in close proximity inside the polymeric matrix boost the ROS production of the antimicrobial film.…”
Section: Spr Simulation Of Aunrssupporting
confidence: 55%
See 2 more Smart Citations
“…It has been shown from previous work that the electrostatic interaction brings the dyes and the AuNRs together. 15 The overlapping between the absorption of the SPR peaks of AuNRs indicated by the simulation and the dye absorption confirm that all the components of the spectra, can participate in the plasmonic coupling with the dye. Thus, when located in close proximity inside the polymeric matrix boost the ROS production of the antimicrobial film.…”
Section: Spr Simulation Of Aunrssupporting
confidence: 55%
“…14 This method uses 15 mL of a solution containing 9:1 acetone to nanoparticles dispersion (1.5 O.D. ; approximatively 0.65 mM of Au 0 , the optimum concentration based on our previous study 15 ) to swell 30 cm 2 polymeric matrix. The swelling process required an overnight incubation under moderate magnetic stirring, in order to obtain a uniform deposition of the particles.…”
Section: Preparation Of the Antimicrobial Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study [ 70 ], gold nanorods (AuNRs) were embedded with a photosensitizer dye crystal violet (CV) in a polyurethane (PU) matrix to fabricate an effective antimicrobial film. This film was capable of eradicating Gram-negative bacteria E. coli on its surface when exposed to white light.…”
Section: Gold Nanoparticles (Aunps) As Novel Antibacterial Agentsmentioning
confidence: 99%
“…Gold nanoparticles of different shapes and sizes are able to generate reactive oxygen species (ROS) by themselves under a suitable photoactivation source [ 81 , 82 ]. However, in our literature review, we found that AuNPs were linked to a photosensitizer in most of the APDT systems [ 70 , 75 , 78 ]. According to the previously discussed APDT approaches, there is good scientific evidence that combining gold nanoparticles with a photosensitizer has a synergism effect and would perform better in terms of ROS generation.…”
Section: Gold Nanoparticles (Aunps) As Novel Antibacterial Agentsmentioning
confidence: 99%